2021
DOI: 10.1136/gutjnl-2020-323014
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-delivered CD44v6/C1QBP complex drives pancreatic cancer liver metastasis by promoting fibrotic liver microenvironment

Abstract: ObjectivePancreatic ductal adenocarcinoma (PDAC) shows a remarkable predilection for liver metastasis. Pro-oncogenic secretome delivery and trafficking via exosomes are crucial for pre-metastatic microenvironment formation and metastasis. This study aimed to explore the underlying mechanisms of how PDAC-derived exosomes (Pex) modulate the liver microenvironment and promote metastasis.DesignC57BL/6 mice were ‘educated’ by tail vein Pex injection. The intrasplenic injection liver metastasis and PDAC orthotopic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 45 publications
2
90
0
Order By: Relevance
“…As examples, extracellular vesicles-mediated delivery of ITIH4 to target cells regulated cell growth and inflammatory response 42 and extracellular vesicles-mediated delivery of TGF-β, Smad2, and Smad4 modulated neuroinflammation and protected against ischemic stroke. 49 Xie et al 50 also reported that extracellular vesicles-shuttled CD44v6/C1QBP complex can drive liver metastasis of pancreatic cancer. Thus, we next investigated the role of protein cargoes in mediating the beneficial effects of MEVs.…”
Section: Discussionmentioning
confidence: 98%
“…As examples, extracellular vesicles-mediated delivery of ITIH4 to target cells regulated cell growth and inflammatory response 42 and extracellular vesicles-mediated delivery of TGF-β, Smad2, and Smad4 modulated neuroinflammation and protected against ischemic stroke. 49 Xie et al 50 also reported that extracellular vesicles-shuttled CD44v6/C1QBP complex can drive liver metastasis of pancreatic cancer. Thus, we next investigated the role of protein cargoes in mediating the beneficial effects of MEVs.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Stefanius, K. et al report that exosomes from PDAC initiate cell transformation by stimulating NIH/3T3 recipient cells [90]. Xie, Z. et al found the exosome CD44v6/C1QBP derived from PDAC formulate the hepatic metastasis microenvironment [40]. As an important carrier, the functions of exosomes are realized through their contents, and miRNA is one of the most abundant cargo [91].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes can detected in varieties of body uids, including blood, urine, bile, ascites and so on [34,35], therefore, they can be used as the novel templates for tumor diagnostic [36][37][38]. Multiple functions of exosomes in PDAC have been reported [29,[39][40][41], we found that exosomes serve as a "bridge" between PDAC and CAFs, and CAFs are important component of the tumor microenvironment (TME).…”
Section: Introductionmentioning
confidence: 88%
“…Li et al reported that exosomal miRNA-19b-3p from tubular epithelial cells contributed to M1 macrophage activation in kidney damage [ 45 ]. A recent research showed that Pancreatic ductal adenocarcinoma derived exosome carried CD44v6/ C1QBP complex to promote pancreatic cancer liver metastasis [ 46 ]. Ju et al showed that grape exosome-like nanoparticles gradually accumulated in the gut 6 hours after administration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%